Bipartite Toughness and k-Factors in Bipartite Graphs - Guizhen Liu; Jianbo Qian; Jonathan Z. Sun; Rui Xu (International Journal of Mathematics and Mathematical Sciences, 2008)
We define a new invariant tB(G) in bipartite graphs that is analogous to the toughness t(G) and we give sufficient conditions in term of tB(G) for the existence of k-factors in bipartite graphs. We also show that these results are sharp.